Mapping rhetorical dissent: a comparative analysis of the Obergefell opinions - Goźdź-Roszkowski, Stanisław (Comparative Legilinguistics, 2025)
This paper offers a rhetorical analysis of the four dissenting opinions in Obergefell v. Hodges (2015), the landmark U.S. Supreme Court case that extended constitutional protection to same-sex marriage. Drawing on a ten-dimensional coding framework, the study investigates how Justices Roberts, Scalia, Thomas, and Alito construct their dissenting positions not only in legal terms but as distinctive rhetorical performances. The framework includes appeals (ethos, logos, pathos), tone/style, framing devices, intertextuality, figurative language, rhetorical questions, identity and community appeals, and lexical polarity). While united in outcome, the dissents diverge sharply in form, intent, and audience. Roberts adopts a tone of institutional mourning; Scalia mounts a caustic protest; Thomas articulates a doctrinal and philosophical minimalism; and Alito warns against the erosion of pluralism and conscience rights. The analysis shows that judicial dissent operates on multiple discursive levels, revealing divergent conceptions of law, democracy, and cultural identity. By focusing on dissent as a rhetorical genre, this paper contributes to broader debates about constitutional discourse, the function of dissenting opinions, and the interplay between law and persuasion in pluralistic societies.